2019
DOI: 10.1002/ange.201904598
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Peptoid‐Based Cylindrical Micelles Exhibiting Efficient Resonance Energy Transfer in Aqueous Solution

Abstract: Herein we showt hat by appending bulky b-cyclodextrin (CD) groups onto sheet-forming peptoids,w eo btain cylindrical micelles that further assembly into membranes and intertwined ribbons on substrates in aqueous solution, depending on the choice of solution and substrate conditions.I nsitu atomic force microscopy( AFM) shows that micelle assembly occurs in two steps,s tarting with "precursor" particles that transform into worm-like micelles,w hiche xtend and coalesce to form the higher order structures with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…S31). Rhodamine B (RB) was used as the acceptor because it is a well-known guest molecule for CD (27), and its absorption band exhibits significant overlap with the fluorescence emission peak of DNS donor, thus fulfilling one of the requirements for high FRET efficiency. Because of strong binding between RB and CD cavity, RB can be easily loaded into the CD groups on sheet surfaces.…”
Section: Building a Highly Efficient Fret System Using Poss-peptoidbased 2d Nanocrystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…S31). Rhodamine B (RB) was used as the acceptor because it is a well-known guest molecule for CD (27), and its absorption band exhibits significant overlap with the fluorescence emission peak of DNS donor, thus fulfilling one of the requirements for high FRET efficiency. Because of strong binding between RB and CD cavity, RB can be easily loaded into the CD groups on sheet surfaces.…”
Section: Building a Highly Efficient Fret System Using Poss-peptoidbased 2d Nanocrystalsmentioning
confidence: 99%
“…Inspired by the highly efficient light-harvesting systems in green plants and living organisms, in which well-positioned chromophores and protein complex formed an efficient Förster resonance energy transfer (FRET) system for converting light to chemical stored energy, many synthetic materials have been developed to mimic this natural light-harvesting process by achieving efficient energy transfer from donors to acceptors (24)(25)(26). However, despite great advances that have been made in this area, developing highly efficient light-harvesting systems in aqueous solution rather than in organic environments is still a challenging task (27)(28)(29)(30). On the other hand, while two-dimensional (2D) nanomaterials assembled from sequence-defined molecules have recently received considerable interest because their embedded high information contents offer tremendous potentials in applications (7), organic-inorganic hybrid 2D nanomaterials assembled from these sequence-defined building blocks are extremely rare, and no studies have been reported to develop such hybrid materials as efficient artificial light-harvesting systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By appending bulky β‐cyclodextrin (CD) group on to sheet‐forming N 4‐Cl pe 6 Nce 6 peptoid in Figure 6C, cylindrical micelles first form and further assemble into nanosheets and intertwined ribbons upon different solution and substrate conditions. [ 46 ] A two‐step hierarchical assembly pathway is also shown by in situ AFM, starting with 0D particles which transfer into 1D cylindrical micelles, then 2D nanosheets and three‐dimensional (3D) intertwined ribbons. Moreover, the kinetic of peptoid assembly in this work is highly dependent on the pH and Ca 2+ concentration.…”
Section: Other Linear Peptoid Sequencesmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13] These interactions are dependent on the sequence used and can often be controlled using pH, temperature, electrolytes, solvent, and/or pendant groups. [14][15][16][17][18] When inorganic nanoparticles act as the driving force for assembly, the generated structures are often a result of particle packing and drying effects. In these systems, the structures can be tuned through size, surface chemistry, ligand packing or morphology of the nanoparticles but frequently lack precision and are often limited to 2D films or layered structures of the aforementioned films.…”
mentioning
confidence: 99%